Identifying evidence for past mining and metallurgy from a record of metal contamination preserved in an ombrotrophic mire near Leadhills, SW Scotland, UK. (December 2014) - Mighall, Tim; Martínez Cortizas, Antonio; Silva Sánchez, Noemí; Foster, Ian DL; Singh, Surjit; Bateman, Mark; Pickin, John
This study presents a new 3600-year record of past metal contamination from a bog located close to the Leadhills and Wanlockhead orefield of southwest Scotland. A peat core, collected from Toddle Moss, was radiocarbon ( 14 C) dated and analysed for trace metal concentrations (by EMMA) and lead isotopes (by ICP-MS) to reconstruct the atmospheric deposition history of trace metal contamination, in particular, lead. The results show good agreement with documented historical and archaeological records of mining and metallurgy in the region: the peak in metal mining during the 18th century, the decline of lead mining during the Anglo-Scottish war and lead smelting during the early medieval period. There may also have been earlier workings during the Late Bronze and Iron Ages indicated by slight increases in lead concentrations, the Pb/Ti ratio and a shift in 206 Pb/ 207 Pb ratios, which compare favourably to the signatures of a galena ore from Leadhills and Wanlockhead. In contrast to other records across Europe, no sizeable lead enrichment was recorded during the Roman Iron Age, suggesting that the orefield was not a significant part of the Roman lead extraction industry in Britain. These findings add to the various strands of archaeological evidence that hint at an early lead extraction and metallurgical industry based in southern Scotland. The results also provide further evidence for specific regional variations in the evolution of mining and metallurgy and an associated contamination signal during prehistoric and Roman times across Europe.